ON ANNOUNCEMENT FOR UNIVERSITY WHITEBOARD USING MOBILE APPLICATION - Jasim, Yaser A.; Alsaaigh, Mustafa O.; Flaih, Tawfeeq M.; Saeed, Mustafa Ghanem (CSRID (Computer Science Research and Its Development Journal), 2020)
The university students who use traditional announcement boards nowadays are exposed to various problems. The most severe problem is that the instructors may want to publish an announcement, but they may not exist in university, or maybe they are after a work time. So, they cannot or can inform to the announcement board moment by moment. Moreover, the students should be near the announcement board all the time. The scope of this research is to build a unique mobile application that acts as a digital university announcement board. Where this application mainly consists of two sides; the server-side (PHP with MySQL) and client-side Android Applications. Through using the proposed application, the university staff can send announcements to students directly, and the announcement will be delivered to student devices in real-time with push notification. Instructors will be able to announce one student or a group of students or all the students from different departments and stages. The suggested application was built and tested in the android operating system and the real mobile device.